Mağaza dış ve iç dizaynı, mağaza atmosferi ve bunların tüketici satınalma davranışları üzerine etkileri - Güler, Mehmet (My University, 2001)
The study has three sections; In the first section, the definitions of department store were given and the developments of department store sector were mentioned. In the second section, store exterior design, store interior design and store atmosphere have explained and their components and their attributes have examined. In the third section, a research which about to determine that how much the consumers are interested in store exterior, interior design and store atmosphere, and how these attributes influence the consumer purchase behaviors has developed. In the department stores, too many kinds of merchandises are selling in the same store but in the different departments. In the department stores, all departments are collected under the same management, usually selling non foodstuffs merchandises. The department stores are big scaled retail stores. The store design explains what the store is about to the customers. The store design is the architectural character and the decorative still of the store. Because of the stores have variety about kind, scale and geographical settling it is too hard to make a generalization. Surely the store exterior design protects the interior part of the store from the components. Also the exterior design should give informations about the store to the potential and existing customers. The potential customers saw firstly the exterior part of the store. Store interior design determines, the settings of merchandises in the store and the presentation techniques of merchandises. Interior design should help customers to get merchandises easily. Atmosphere contacts with, visual communication tools, lighting, color, music in designing the environment. Therefore it influences the consumers and this influence reflects directly to the purchase behaviors. Consumers instore feelings effects the time, and the money that consumers spend in the store.
Keywords: Mağaza dekorasyonu; Tüketici Davranışı